Treatment Results of Extracranial Malignant Germ Cell Tumor with Regimens of Cisplatin, Vinblastine, Bleomycin or Carboplatin, Etoposide, and Bleomycin with Special Emphasis on the Sites of Vagina and Testis - Jen-Yin Hou; Hsi-Che Liu; Ting-Chi Yeh; Jin-Cherng Sheu; Kuan-Hao Chen; Ching-Yi Chang; Der-Cherng Liang (Pediatrics and Neonatology)
The survival of children with malignant germ cell tumor (GCT) increased over the past 2 decades with platinum-based chemotherapy. This report has three objectives: (1) comparison of PVB (cisplatin, vinblastine, and bleomycin) with JEB (carboplatin, etoposide, and bleomycin) regimens; (2) treatment modality of vaginal GCT; and (3) management of stage I testicular yolk sac tumor (YST) in boys under 2 years old. Methods: From January 1, 1987 to December 31, 2010, 81 patients with malignant extracranial GCT were treated. Two consecutive protocols, PVB followed by JEB, were used. Girls with vaginal YST received minimal surgery and chemotherapy. Boys under 2 years old with Stage I testicular YST received surgery with or without chemotherapy. Results: As of June 30, 2012, the 10-year overall survival (OS) was 95 ± 3% (standard error) and the event-free survival (EFS) was 88 ± 4%. With PVB, 35 patients had 10-year OS of 91 ± 5% and EFS of 89 ± 5%. With JEB, 25 patients had 7-year OS of 96 ± 5% and EFS of 96 ± 5%. All five girls with vaginal YST were cured with vagina-preserved strategy. In 32 boys age under 2 years old with stage I YST, 16 with light chemotherapy were all in EFS, whereas two of 16 patients without chemotherapy relapsed. After PVB, six patients developed nephrotoxicity and one had pulmonary fibrosis. Conclusion: Girls with vaginal YST who received minimal surgery and chemotherapy had excellent prognosis and sexual organs were preservable. Light chemotherapy after surgery is a treatment option for boys under 2 years old with stage I YST to decrease relapse rate. Both JEB and PVB are effective. JEB resulted in more myelosuppression but otherwise less serious long-term toxicity than PVB.